Alone in the Universe - Smith, Howard (Zygon, 2016)
We are probably alone in the universe—a conclusion based on observations of over 4,000 exoplanets and fundamental physical constraints. This article updates earlier arguments with the latest astrophysical results. Since the discovery of exoplanets, theologians have asked with renewed urgency what the presence of extraterrestrial intelligence (ETI) says about salvation and human purpose, but this is the wrong question. The more urgent question is what their absence says. The “Misanthropic Principle” is the observation that, in a universe fine-tuned for life (“Anthropic Principle”), the circumstances necessary for intelligence are rare. Rabbis for 2,000 years discussed the existence of ETI using scriptural passages. We examine the traditional Jewish approaches to ETI, including insights on how ETI affects our perception of God, self, free-will, and responsibility. We explore the implications of our probable solitude, and offer a Jewish response to the ethical lessons to be drawn from the absence of ETI.